Management model for measurement infrastructure - Battisti, Gerson (2005)
The evaluation of metric of performance is useful in the evaluation of protocols, in the improvement of applications, in the content choice, among others. The obtaining of these metrics, it continues being a complex task because most of the time there are not appropriate tools for such. The measurement infrastructures appear as a form of endowing the networks of computers with instruments that facilitate the acquisition of these metrics. This work evaluates a group of measurement infrastructures, where it is possible to observe that the treatment showed to the management of such infrastructures is varied. They do not possess a group of standardized management functions. Based on that, this article presents a proposal of a management model for measurement infrastructures. The proposed model maintains the administrative independence of the present points in the infrastructure, but it allows the interaction among them by means of specific management functions